2021
DOI: 10.20546/ijcmas.2021.1001.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Organic and Inorganic Seed Priming Method on Growth, Yield and Quality Parameters of Field Pea (Pisum sativum L.)

Abstract: Pulses are referred to as poor man's meat, as they are major sources of protein and compliment the stable cereals in the diet with essential nutrients. They occupy pivotal position particularly in developing countries like India, where most of the population is vegetarian. Pulses belong to the family Leguminosae and subfamily Papilionoidaceae. They provide 22-24 per cent protein and the seeds are considered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Gunasekar et al [8] found an increase in plant height, number of branches per plant, and pod length when black gram seeds are treated with Pongamia leaf extract. Abdul Wajid et al [9]. also found in their experiment that plant height and number of branches per plant has been increased when field pea seeds were treated with pongamia leaf extract.…”
Section: Physiological Parametersmentioning
confidence: 92%
“…Gunasekar et al [8] found an increase in plant height, number of branches per plant, and pod length when black gram seeds are treated with Pongamia leaf extract. Abdul Wajid et al [9]. also found in their experiment that plant height and number of branches per plant has been increased when field pea seeds were treated with pongamia leaf extract.…”
Section: Physiological Parametersmentioning
confidence: 92%
“…Peas contain symbiotic bacteria called Rhizobia within root nodules of their Root system (in most of the legume crops). These rhizobium bacteria have the special ability to fix N2 from atmospheric, molecular nitrogen (N2) into Ammonia (NH3) [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%